Pengaruh Motivasi dan Kepuasan Kerja terhadap Kinerja Karyawan di PT Daksa Sinergi Tangerang Selatan - Ratna Sari (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Employee performance is a critical factor in determining the success and competitiveness of organizations. In modern business environments, motivation and job satisfaction are considered key determinants that influence how effectively employees perform their duties. Low motivation and dissatisfaction can lead to reduced productivity, high turnover, and poor organizational outcomes. This study aims to examine the influence of motivation and job satisfaction on employee performance at PT Daksa Sinergi Tangerang Selatan. A quantitative approach with a survey method was employed to collect empirical data. The population consisted of all 57 employees of the company, who were entirely included as the research sample using a saturated sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using SPSS version 25, including validity and reliability tests, classical assumption tests, multiple linear regression, and t-test and F-test analyses. The findings indicate that both motivation and job satisfaction have a positive and significant impact on employee performance. Employees who are highly motivated and experience job satisfaction tend to show greater productivity, responsibility, and commitment to organizational goals. These results underscore the importance of human resource management strategies that enhance intrinsic motivation and foster a supportive work environment. Practically, companies should focus on providing appropriate rewards, opportunities for career development, and harmonious workplace relationships to sustain and improve employee performance continuously.